Nutrient/TOR-dependent regulation of RNA polymerase III controls tissue and organismal growth in Drosophila. - Marshall, L.; Rideout, E.J.; Grewal, S.S. (The EMBO Journal, 2012)
The nutrient/target-of-rapamycin (TOR) pathway has emerged as a key regulator of tissue and organismal growth in metazoans. The signalling components of the nutrient/TOR pathway are well defined; however, the downstream effectors are less understood. Here, we show that the control of RNA polymerase (Pol) III-dependent transcription is an essential target of TOR in Drosophila. We find that TOR activity controls Pol III in growing larvae via inhibition of the repressor Maf1 and, in part, via the transcription factor Drosophila Myc (dMyc). Moreover, we show that loss of the Pol III factor, Brf, leads to reduced tissue and organismal growth and prevents TOR-induced cellular growth. TOR activity in the larval fat body, a tissue equivalent to vertebrate fat or liver, couples nutrition to insulin release from the brain. Accordingly, we find that fat-specific loss of Brf phenocopies nutrient limitation and TOR inhibition, leading to decreased systemic insulin signalling and reduced organismal growth. Thus, stimulation of Pol III is a key downstream effector of TOR in the control of cellular and systemic growth.